PENGENAAN PAJAK PENGHASILAN TERHADAP YOUTUBER DI INDONESIA - Gunardi Lie; Indah siti aprilia; Moody Rizqy Syailendra P. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Youtube is a media platform that is currently widely use and has become a platform fot making profits and jobs. The principle of taxation in Indonesia is that everyone who has income needs to be taxed, that’s why the Government sees the potential for tax collection on Youtuber production. The research method use normative juridical approach with a statutory approach and a fact approach. The conclution obtained form this study is that youtubers are included in the tax subject, then the tax objext of the youtuber profession is categorized as a tax object and can be classified into the group of sources of income from freework. The calculation of the amount of tax is based on the Regulation of the Director General of Taxes Number PER-17/PJ/2015. However, in its implementation, the process of supervision of professional taxpayers has not yet created legal certainty, the lack of a supervision process with a social network analytics system has not been implemented, where this tax officer is still conducting manual supervision.